2020
DOI: 10.1088/1742-6596/1456/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Competency of vocational schools required by construction industry in consultants’ supervisor

Abstract: This study aims to find out how much the needs of personal competence, basic knowledge, and work skills of vocational graduates Construction and Property Technology Expertise Program by the world of Construction Services Industry which is engaged in the Field Supervision Consultant. The method used to select the sample is the quota sampling and snowball sampling method where the sample is 15 companies with a population of 136 companies. The results of this study draw conclusions as follows: (1) overall compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 1 publication
6
18
0
Order By: Relevance
“…As a formal education that develops educated, skilled, and competent VHS graduates' (Daryono et al, 2021;Nurtanto, Arifin, Sofyan, Warju & Nurhaji, 2020), VHS is deemed necessary to improve their quality. The current competency of VHS graduates is still not able to bring them to excel (Ayadat, Ahmed, Chowdhury & Asiz, 2020) and become winners in the increasingly competitive world of work competition (Daryono, Yolando, Jaedun & Hidayat, 2020). Motivation and the way of thinking of students who tend to look for work after graduation and do not think of looking for other alternatives such as opening their jobs or doing entrepreneurship still dominate the minds of most VHS graduates.…”
Section: Introductionmentioning
confidence: 99%
“…As a formal education that develops educated, skilled, and competent VHS graduates' (Daryono et al, 2021;Nurtanto, Arifin, Sofyan, Warju & Nurhaji, 2020), VHS is deemed necessary to improve their quality. The current competency of VHS graduates is still not able to bring them to excel (Ayadat, Ahmed, Chowdhury & Asiz, 2020) and become winners in the increasingly competitive world of work competition (Daryono, Yolando, Jaedun & Hidayat, 2020). Motivation and the way of thinking of students who tend to look for work after graduation and do not think of looking for other alternatives such as opening their jobs or doing entrepreneurship still dominate the minds of most VHS graduates.…”
Section: Introductionmentioning
confidence: 99%
“…Data collection techniques used questionnaires and tests, questionnaires were used to measure variable responses (Daryono et al, 2020;Setyadi et al, 2021) to experts in the form of Teaching games for understanding (TGfU) ap-proaches and higher-order thinking skills (HOTS) in basketball learning. The data collection instruments consist of 1) Test instrument, a test in the form of multiple-choice (dichotomies 0 and 1) with five answer choices, which refers to indicators of higher-order thinking skills totaling 25 questions; 2) Validation sheet, carried out by two experts, namely: instrument expert for validation of test instruments and evaluation expert for validation of TGfU and HOTS assessments (Subay et al, 2019), Furthermore, the validation was carried out by three sports teachers to determine the practicality and response of teachers as teachers in the school environment (Riyanto & Widiyanto, 2021).…”
Section: Data Collection Techniques and Instrumentmentioning
confidence: 99%
“…Based on the construct validity test or the feasibility of implementing the basketball learning model using a questionnaire instrument, with Explanatory Factor Analysis (EFA) it was found that the questionnaire instrument was by the content validity of the experts (Daryono et al, 2020;Hidayat et al, 2018). The assessment of the model using a questionnaire instrument was carried out by 3 judges or raters including physical education teachers to see if the model was easy, practical, and safe to use.…”
Section: Learning Model Trial: Construct Validitymentioning
confidence: 99%
“…Vocational education is part of the education system that prepares students to be able to work in certain fields (Daryono et al, 2021;Pratomo et al, 2020;Triyono et al, 2020). In secondary education units, Vocational High Schools (VHS) have a goal to improve intelligence (Coetzer et al, 2020;Han et al, 2015;Supriyadi et al, 2020), knowledge (Daryono, Yolando, et al, 2020;Habiyaremye, 2020;Wheelahan, 2015), personality, noble character, and skills (Beicht & Walden, 2019;Boonk et al, 2020) to live independently and attend further education in accordance with their profession (Daryono et al, 2021;Nurtanto et al, 2020). It is hoped that VHS graduates will be able to meet the demands of a competent workforce in order to increase productivity and efficiency and be able to compete in the international labor market in the era of globalization (Forum Económico Mundial, 2019;Saifurrahman et al, 2021;Tayibnapis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%